2013
DOI: 10.1590/1982-43272355201314
|View full text |Cite
|
Sign up to set email alerts
|

Consequences of Exposure to Domestic Violence for Children: A Systematic Review of the Literature

Abstract: The aim of this study was to carry out a systematic review of the literature on the consequences of exposure to domestic violence – DV for children. The period 2005-2011 was searched in Medline, Lilacs, Scielo, Web of Science, Dialnet, Redalyc, Google Scholar and PsycInfo, using the following descriptors: intimate partner violence , domestic violence , violence descriptors ( physical , sexual, psychological ), and child , exposure or witness . The author, country, methodology, journal and the consequences … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 18 publications
0
23
0
3
Order By: Relevance
“…The majority of women observed that the controlling tactics and abuse used towards them were also being used on children to establish an atmosphere of fear and unpredictability, and that the violence they experienced traumatized their children. This is also a clear finding from a metaanalysis of the research studies (Lourenço et al, ).…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…The majority of women observed that the controlling tactics and abuse used towards them were also being used on children to establish an atmosphere of fear and unpredictability, and that the violence they experienced traumatized their children. This is also a clear finding from a metaanalysis of the research studies (Lourenço et al, ).…”
Section: Discussionmentioning
confidence: 54%
“…Children who witness, live with, or is exposed to domestic violence is the terminology often used to recognize that children may not be the primary target, but they are nevertheless significantly impacted by intimate partner violence (Levendosky, Bogat, & Martinez‐Torteya, ). The indirect nature of the harm may obfuscate the responsibility of fathers for harming their children through undermining the child's mother (physically and emotionally), through comprising the functioning of the family and creating an atmosphere of fear in which children are unable to thrive (Lourenço et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…More recent studies have shown similar outcomes, presenting a prevalence of depressive symptoms, insecurity, and post-traumatic stress disorder (75.8%), followed by behavioral problems and aggression (32.6%), and declining academic performance and bullying (20%) [14], or concluding that exposure to IPV was positively associated with child adjustment problems for externalizing and internalizing behaviors [15,16]. IPV is a form of child maltreatment, with harmful and long-term consequences for health and well-being [17,18].…”
Section: Violence Experienced By Children In the Context Of Ipvmentioning
confidence: 75%
“…Other researchers such as Evans and colleagues; Wentworth and Middleton; and Lourencoand colleagues [17][18][19] share the same finding concerning the influence of home to student performance and posit that lack of support from home leads to a downslide or decline in the academic performance of students. This normally happens in urban areas where most working parents are too busy to care for their children's performance.…”
Section: Discussionmentioning
confidence: 85%